Handbook of Academic Learning : Construction of Knowledge. - Phye, Gary D. (Elsevier, 1996)
The Handbook of Academic Learning provides a comprehensive resource for educational and cognitive psychologists, as well as educators themselves, on the mechanisms and processes of academic learning. Beginning with general themes that cross subject and age level, the book discusses what motivates students to learn and how knowledge can be made personal for better learning and remembering. Individual chapters identify proven effective teaching methods for the specific domains of math, reading, writing, science, and critical problem solving, how students learn within those domains, and how learn.